A novel bispecific antibody therapy against colorectal cancer.
'Colorectal cancer' (CRC) is one of the leading causes of cancer-related deaths in Europe. A new antibody-based therapy developed using novel patient-derived screening technology, promises to specifically treat CRC patients with reduced side-effects.